Myocardial Injury After Noncardiac Surgery (MINS) in Vascular Surgical Patients: A Prospective Observational Cohort Study. Issue 2 (August 2018) - Biccard, Bruce M.; Scott, David Julian Ashbridge; Chan, Matthew T. V.; Archbold, Andrew; Wang, Chew-Yin; Sigamani, Alben; Urrútia, Gerard; Cruz, Patricia; Srinathan, Sadeesh K.; Szalay, David; Harlock, John; Tittley, Jacques G.; et al.
Abstract : Objective: To determine the prognostic relevance, clinical characteristics, and 30-day outcomes associated with myocardial injury after noncardiac surgery (MINS) in vascular surgical patients. Background: MINS has been independently associated with 30-day mortality after noncardiac surgery. The characteristics and prognostic importance of MINS in vascular surgery patients are poorly described. Methods: This was an international prospective cohort study of 15, 102 noncardiac surgery patients 45 years or older, of whom 502 patients underwent vascular surgery. All patients had fourth-generation plasma troponin T (TnT) concentrations measured during the first 3 postoperative days. MINS was defined as a TnT of 0.03 ng/mL of higher secondary to ischemia. The objectives of the present study were to determine (i) if MINS is prognostically important in vascular surgical patients, (ii) the clinical characteristics of vascular surgery patients with and without MINS, (iii) the 30-day outcomes for vascular surgery patients with and without MINS, and (iv) the proportion of MINS that probably would have gone undetected without routine troponin monitoring. Results: The incidence of MINS in the vascular surgery patients was 19.1% (95% confidence interval (CI), 15.7%–22.6%). 30-day all-cause mortality in the vascular cohort was 12.5% (95% CI 7.3%–20.6%) in patients with MINS compared with 1.5% (95% CI 0.7%–3.2%) in patients without MINS ( P < 0.001). MINS was independently associated with 30-day mortality in vascular patients (odds ratio, 9.48; 95% CI, 3.46–25.96). The 30-day mortality was similar in MINS patients with (15.0%; 95% CI, 7.1–29.1) and without an ischemic feature (12.2%; 95% CI, 5.3–25.5, P = 0.76). The proportion of vascular surgery patients who suffered MINS without overt evidence of myocardial ischemia was 74.1% (95% CI, 63.6–82.4). Conclusions: Approximately 1 in 5 patients experienced MINS after vascular surgery. MINS was independently associated with 30-day mortality. The majority of patients with MINS were asymptomatic and would have gone undetected without routine postoperative troponin measurement. Abstract : Supplemental Digital Content is available in the text